2000
DOI: 10.2460/ajvr.2000.61.14
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor down-regulation in neutrophils of periparturient cows

Abstract: Reduced GR expression in blood neutrophils of periparturient dairy cows was associated with increased serum cortisol concentrations, leukocytosis, and neutrophilia. Thus, GR down-regulation in neutrophils may be involved in periparturient neutrophil dysregulation and may cause increased susceptibility to mastitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 25 publications
9
34
0
1
Order By: Relevance
“…The level of glucocorticoid receptors is a major factor in determining the sensitivity of cells to glucocorticoids. The periparturient response to glucocorticoids might be diminished in bovine PMN and monocytes because glucocorticoid receptor expression is downregulated in these cells in the periparturient period (78,79). Studies in humans indicate that the maternal HPA axis is blunted during pregnancy and the immediate postpartum period.…”
Section: Sympathoadrenal Activity Around Parturition and During Intramentioning
confidence: 99%
“…The level of glucocorticoid receptors is a major factor in determining the sensitivity of cells to glucocorticoids. The periparturient response to glucocorticoids might be diminished in bovine PMN and monocytes because glucocorticoid receptor expression is downregulated in these cells in the periparturient period (78,79). Studies in humans indicate that the maternal HPA axis is blunted during pregnancy and the immediate postpartum period.…”
Section: Sympathoadrenal Activity Around Parturition and During Intramentioning
confidence: 99%
“…PCV% and Hb content (gm/dl) showed a significant decrease during peri-parturient periods, that was attributed to anemia due to stress of pregnancy and parturation (Daramola et al, 2004). Elevation of serum cortisol around parturition (Preisler et al, (2000) and Kim et al, (2005), resulting in a significant decrease in total leucocytic count, lymphocyte % and neutrophils % in the early lactating group compared with late pregnant one. The significant decrease of serum calcium level after birth was coincides with that observed by Zeinab (2007) and Hagawane et al (2009) whose suggested that deficiency may be returned to improper food metabolite absorption from gastrointestinal tract, insufficient mobilization of Ca from the skeleton, excessive Ca loss in urine and draining of high percent of Ca and phosphorus Hassan(1988) in colostrum during excessive milking soon after birth.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, neutrophils may be responsible for excessive inflammation and tissue damage observed in the BRDC associated with transportation-stressed cattle (Maheswaran et al, 1992;Lekeux, 1995;Wessely-Szponder et al, 2004). A profound leukocytosis, marked by neutrophilia may occur in conjunction with a decrease in the number of lymphocytes (Blecha et al, 1984;Preisler et al, 2000), indicating a disruption of neutrophil homoeostasis in response to stress in cattle. There is also evidence that antibacterial functions may also be attenuated in neutrophils during a viral infection (Yates, 1982).…”
Section: Haematological Cell Changes Indicative Of a Stress Responsementioning
confidence: 99%
“…Gene expression regulation results from the binding of cortisol to its GR in the cytoplasm of target cells, with subsequent translocation of hormone-activated receptors into the nucleus and modulation of gene transcription by direct (receptor-DNA) and indirect (receptor-protein-DNA) interactions in regulatory regions of cortisol-sensitive genes (Preisler et al, 2000;Weber et al, 2006). In addition, bovine neutrophils have been shown to exhibit differential expression of genes important to roles of immune function, apoptosis, tissue remodelling, and various metabolic and cellular functions in response to glucocorticoids in vitro and in vivo (Burton et al, 2005).…”
Section: Gene Expression Changes During Transportation Stressmentioning
confidence: 99%